2020
DOI: 10.21203/rs.2.24235/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sediment microbial communities contribute to shrimp intestine microbiota in cultural pond ecosystems

Abstract: Background Microorganisms in a shrimp cultural pond ecosystem (SCPE) play important roles for animal and environmental health. While the microbial diversity and assembly mechanism, and how communities of multiple habitats contribute to the SCPE metacommunity are poorly understood. Here, we analyzed phylogenetic structure of 792 samples of three habitats (water, shrimp intestine and sediment) from 88 shrimp cultural ponds across six regional sites in China. Results We show that the microbial communities of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
1
0
0
Order By: Relevance
“…Here, we observed a more substantial impact of the biological (organ) on microbiota structure than the environmental (pond) factor. Consistent with this pattern, it has been shown that sediment microbes are major sources for shrimp gut commensals in cultural pond ecosystems [ 65 ]. Also importantly, the microorganisms in shrimp aquaculture ponds could be associated with shrimp disease occurrence [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 55%
“…Here, we observed a more substantial impact of the biological (organ) on microbiota structure than the environmental (pond) factor. Consistent with this pattern, it has been shown that sediment microbes are major sources for shrimp gut commensals in cultural pond ecosystems [ 65 ]. Also importantly, the microorganisms in shrimp aquaculture ponds could be associated with shrimp disease occurrence [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 55%